Resolving Statelessness: Geopolitical and Humanitarian Dimensions of the Rohingya Repatriation Effort (Global Journal of Human-Social Science, 2025)
The Rohingya crisis exposes the ineffectiveness of the international community in preventing systematic statesponsored persecution of vulnerable populations. Decades of exclusion and violence in Myanmar became a public crisis in 2017 when over a million people from the Rohingya minority fled to Bangladesh. This mass displacement has become one of the greatest humanitarian crises of the 21st century, placing tremendous pressure on Bangladesh’s socio-economic infrastructure while exposing significant shortcomings in global systems of accountability and justice. At the heart of this crisis is Myanmar’s 1982 Citizenship Law, which codified the Rohingya’s statelessness, blocking access to fundamental rights and embedding patterns of violence and displacement. And little is moving forward despite global condemnation and a legal challenge involving the International Court of Justice. Myanmar’s refusal to repatriate, meanwhile, has long collided with geopolitical roadblocks, including major allies’ vetoes, and has effectively brought accountability and the prospect of sustainable repatriation to a standstill. Critically drawing on work in history, social science, and international relations, the paper examines the layers of historical, socio-economic, and geo-political complexity underlying the surface of the crisis and argues for a multi-disciplinary, multi-dimensional, rightsbased countenancing of its legal implications and human cost. As such, immediate legal reforms taking place in Myanmar, fair burden-sharing, and more concerted action both internationally and regionally are necessary to bring about justice for the Rohingya people and viable pathways to resolution.